Review on Intrusion detection system in centralised network - *, Pankaj; garg, Puneet (IJRDO -Journal of Computer Science Engineering, 2017)
The appearance of mobile computing devices such as laptops, smart phones grew people started to expect to gain network connectivity. As a result several groups started working on means to accomplish this task. This led to wireless LANs being marketed by several companies however this proposed standard could be used in two ways, one with the presence of a base station and the other without the presence of a base station. In the latter case the computers would communicate to each other directly. This is called as an ad-hoc network. A further specified case of ad-hoc networks is when the nodes i.e., computers in this case are mobile. In these cases each node consists of a host and a router on the same device. This means that the nodes form a network without the use of an external routing device.